Emotional Intelligence Development and Learning Engagement in a Private Middle School across Student Learning Motivation in the Context of Indonesian Culture - Santoso, Maria Susanti; Susanti, Lidia (STIPAK Malang, 2024)
The study was undertaken after students in Indonesia had returned to in-person classroom instruction. Remote learning that lasted nearly 30 months has taken a toll on the emotional maturity evidenced by the increasing conflicts and self-insecurity as well as the low learning engagement that are manifested in students’ low participation. This study was conducted on 235 grade 7- 9 students in a private middle school in Indonesia to find out the effects of emotional intelligence and learning engagement on students’ learning motivation. The findings reveal that the study has a validity and consistency in terms of the positive relationship between emotional intelligence and learning engagement and their effects on students’ learning motivation. In terms of emotional maturity, the findings also divulge that emotional immaturity resulted from the lack of stimulation during remote learning. Institutions can enhance educational outcomes by providing teachers and students with support through school counseling services and training in learning strategies, tailored to identify and meet students' needs. Teachers, in turn, can cultivate a more student-centered approach by designing engaging activities that resonate with students' interests, building close relationships to encourage active participation and linking curriculum content to students' daily lives to boost their engagement. Meanwhile, students can be encouraged to develop a deeper understanding of their own and others' emotions, learning to interpret non-verbal cues like facial expressions and tone of voice, practicing empathetic communication, and asking thoughtful questions. To broaden the applicability of these findings, researchers should consider conducting similar studies across various age groups and in multiple Junior High Schools, as the current study's insights are based on observations from just one school.